Improving Access to and Delivery of Maternal Health Care Services to Prevent Postpartum Hemorrhage in Selected States in Nigeria: Human-Centered Design Study - Bosun Tijani; Uchenna Igbokwe; Temi Filani; Adefemi Adewemimo; Lola Ameyan; Martins Iyekekpolor; Steven Karera; Olatunji Oluyide; Emmanuela Ezike; Temidayo Akinreni; Obruche Ogefere; Victor Adetimilehin; et al. (JMIR Human Factors)
Abstract BackgroundA significant cause of postpartum hemorrhage (PPH) is access to and delivery of maternal health care services. Several multisectoral strategies have been deployed to address the challenges with little success, thereby necessitating the use of human-centered design (HCD) to enhance health care delivery, particularly in PPH management. ObjectiveThis study aims to develop facility-level solutions for optimizing uterotonic supply chain systems and health service delivery in PPH management through an HCD approach in selected Nigerian states. MethodsThe research used a four-phase HCD methodology: (1) co-research, (2) co-design, (3) co-refinement, and (4) implementation. However, this paper focused on the first 3 phases. In the co-research phase, 203 interviews were conducted, involving 80 pregnant women and nursing mothers, 97 health care workers, and 26 key stakeholders. Additionally, 33 sites were observed across a 3-level continuum of care. Interviews and focus group discussions revealed insights into the distribution of health workers and observed PPH cases, alongside knowledge and administration of uterotonics. Data analysis was carried out using three key steps: (1) identifying key themes from the collected data, (2) developing insight statements that encapsulate these themes, and (3) translating each insight statement into actionable design opportunities. ResultsAbout 150 ideas were produced and translated into 12 solution prototypes in the co-design phase. Progressive refinement following feedback from 140 stakeholders led to the selection of three final solutions: (1) implementing a referral linkage system to improve the transportation of pregnant women to nearby health facilities, (2) increasing demand for antenatal care services among pregnant women and their families, and (3) delivering a comprehensive uterotonic logistics management program for streamlined uterotonic storage and management. ConclusionsThis approach aligns with global health trends advocating for HCD integration in health care programming and aims to empower local champions to drive sustainable improvements in maternal health outcomes. Judicious implementation of the developed prototypes across the states can strengthen clinical care and potentially reduce maternal health service delivery gaps.